PROGRAM PENGALAMAN LAPANGAN (PPL) DI PERPUSTAKAAN SEKOLAH DALAM MENDUKUNG VISI UPI - Hadiapurwa, Angga; Johan, Riche Cynthia; Suhardini, Dini; Rusmono, Doddy (Prodi Teknologi Pendidikan, 2018)
Abstract. As one of teachers colleges that has a vision as a leading and outstanding univer-sity in education field, UPI is expected to contribute to the progress of education, especially that of UPI partner schools. To strengthen the vision and give provision to UPI students, the field experi-ence program is held in school library. Library and Information Science Study Program held PPL in school library for a full semester in 2017. This study aimed to describe PPL activities in school libraries, including planning, implementation and monitoring. This study used descriptive method with quantitative approach. The respondents were PPL teacher supervisors. The implementation (planning, implementation and monitoring) of PPL in school library supported the achievement of UPI vision. It was based on the statement of teacher supervisors who stated that PPL implementa-tion in school library was in accordance with the vision of UPI as a leading and outstanding uni-versity in education field. This study also resulted in some recommendations for next PPL activi-ties, which highlighted the requirement to strengthen studentsâ€™ competencies as future school li-braries, especially on managerial and educational competencies.Â Abstrak. UPI sebagai salah satu LPTK yang mempunyai visi sebagai universitas pelopor dan unggul pada bidang pendidikan diharapkan dapat berkontribusi pada kemajuan pendidikan, terutama sekolah mitra UPI. Program Studi Perpustakaan dan Ilmu Informasi pada tahun 2017 menyelenggarakan Program Pengalaman Lapangan (PPL) di perpustakaan sekolah selama satu semester penuh. Permasalahan pokok penelitian ini adalah: â€œBagaimanakah implementasi (perencanaan, pelaksanaan dan pemantauan) PPL di perpustakaan sekolah dalam mendukung visi UPI sebagai universitas pelopor dan unggul pada bidang pendidikan?â€ Metode yang digunakan dalam penelitian ini yaitu metode deskriptif dengan pendekatan kantitatif. Responden penelitian ini adalah guru pamong PPL. Implementasi PPL di perpustakaan sekolah mendukung pencapaian visi UPI, hal tersebut berdasarkan pernyataan guru pamong menyatakan penyelenggaraan PPL di per-pustakaan sekolah sangat sesuai dengan visi UPI sebagai universitas pelopor dan unggul pada bi-dang pendidikan. Rekomendasi pada kegiatan PPL selanjutnya yaitu masih perlu penguatan kom-petensi mahasiswa sebagai calon pustakawan sekolah, terutama pada kompetensi manajerial dan kependidikan.